Phytochemical analysis and preclinical toxicological, antioxidant, and anti-inflammatory evaluation of hydroethanol extract from the roots of Harpalyce brasiliana Benth (Leguminosae). (10th August 2022) - Torres-Rêgo, Manoela; Aquino-Vital, Ana Karoline Silva de; Cavalcanti, Felipe França; Rocha, Enos Emanuel Azevedo; Daniele-Silva, Alessandra; Furtado, Allanny Alves; Silva, Diana Pontes da; Ururahy, Marcela Abbott Galvão; Silveira, Edilberto Rocha; Fernandes-Pedrosa, Matheus de Freitas; Araújo, Renata Mendonça
Abstract: Ethnopharmacological relevance: Harpalyce brasiliana Benth (Leguminosae) is a shrub endemic to Brazil, popularly known as "snake's root." This species is used in folk medicine for the treatment of inflammation and snakebites. However, up to now there is no scientific research to justify its popular use. The study aimed to characterize the phytochemical profile of the hydroethanol extract from the roots of  H. brasiliana  (Hb), to evaluate its antioxidant and anti-inflammatory potential, as well as to investigate its cytotoxicity and acute toxicity. Materials and methods: The extract was obtained by maceration method using a solution of ethanol:water (70: 30, v/v). The phytochemical profile was obtained by liquid chromatography coupled to mass spectrometry. The cytotoxicity of extract (31–2000 μg/mL) was evaluated in vitro, by the 3-methyl-[4-5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide (MTT) method using murine macrophage and fibroblast cell lines (RAW 247.6 and 3T3, respectively) and by the hemolytic assay. For the in vivo acute toxicity, the extract (2000 mg/kg) was administered and after 14 days the weight (body and organs) and hematological and biochemical parameters were analyzed. Chemical free radical scavenging effect of the extract (125–2000 μg/mL) was investigated through diphenylpicryl hydrazine reduction, total antioxidant capacity, reducing power, hydroxyl radical scavenging, and iron and copper chelating assays. In vitro anti-inflammatory effect of the extract (125, 500, and 2000 μg/mL) was demonstrated through of nitric oxide (NO) analyzed in lipopolysaccharides stimulated RAW 264.7 cells. In vivo anti-inflammatory activities were evaluated in carrageenan-induced paw edema and zymosan-air-pouch models, with gavage administration (post-treatment) of extract at 100, 200, and 400 mg/kg. For the first animal model, the anti-edematogenic activity and myeloperoxidase (MPO) levels were investigated, while in the zymosan-air-pouch model the leukocyte number, MPO, total protein and pro-inflammatory cytokine (IL-1β, IL-6, and TNF-α) levels were quantified. In addition, the oxidative parameters such as malondialdehyde (MDA) and reduced glutathione (GSH) were determined. Results: The phytochemical profile revealed the presence of 20 compounds, mainly prenylated and geranylated pterocarpans. The extract demonstrated no cytotoxicity in erythrocytes, macrophages and fibroblasts cells at the tested concentrations, as well as no sign of toxicity and mortality or significant alterations on the hematological and biochemical parameters in the acute toxicity model. The extract was also able to neutralize chemical free radicals, with copper and iron chelating effect. For the NO dosage, the extract evidenced the reduction of expression of NO after the administration of the extract (500 and 2000 μg/mL). The edematogenic model revealed a decrease in paw edema and MPO level, while the zymosan-air-pouch model evidenced a reduction of leukocyte number (especially of polymorphornuclears), MPO production, and total protein and cytokine levels, and demonstrated the antioxidant effect through a decrease in MDA and increase in GSH parameters. Conclusion: This approach demonstrates for the first time that Hb is not cytotoxic, has low acute toxicity, and possesses antioxidant and anti-inflammatory properties in preclinical analyses, corroborating its popular use. Graphical abstract: Image 1 Highlights: 20 compounds were identified of hydroethanol extract from the roots of Harpalyce brasiliana . The extract is not cytotoxic and has low acute toxicity. The extract demonstrated antioxidant and anti-inflammatory potential in vitro/vivo.